ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI ULANG KONSUMEN PADA PT USAHA SAUDARA MANDIRI TANGERANG - Octafiani, Fandina; Fatururrahman, Mujtabah (POLITEKNIK LP3I JAKARTA, 2025)
This research aims to identify the factors that influence consumer repurchase intention, determine the most dominant factor at PT Usaha Saudara Mandiri, and analyze the efforts of the company's marketing management in maintaining consumer repurchase interest. The method applied in this research is a quantitative descriptive analysis method, carried out by describing the collected data to be analyzed and processed using numerical calculations. Data processing in this study was conducted through simple tabulation analysis to observe the percentage of respondents selecting certain categories. In this simple tabulation analysis, the obtained data is totaled by frequency and converted into percentages. The main purpose of this analysis is to provide an illustration of the data collected by the researcher. The research, which involved 94 consumer respondents who had purchased products from PT Usaha Saudara Mandiri, showed that the factors influencing repurchase intention were product quality (16%), price (70.2%), distribution (7.4%), and commission (6.4%). Thus, it can be concluded that the most influential factor on consumer repurchase intention at PT Usaha Saudara Mandiri is the price factor. The company's marketing management efforts to maintain consumer repurchase interest include providing satisfactory aftersales service. This study is expected to serve as a reference and evaluation for improving the quality of products, pricing, distribution, or promotion in order to increase consumer repurchase interest.